Materials Analyzing Students' Scientific Literacy Abilities: Does It Impact Their Ability to Complete the Learning Process? - Tasa Ratna Puri; Muhammad Reyza Arief Taqwa; Boby syefrinando (International Journal of Education and Teaching Zone, 2024)
This research was conducted to analyze how students' scientific literacy abilities are seen from their ability to solve physics questions on work and energy. The research design used is quantitative research with descriptive methods (quantitative descriptive). The population used in this research was the entire class X of SMK N 3 Tanjung Jabung Barat. The sampling technique in this research is purposive sampling because the initial data obtained from the entire population is normally distributed and homogeneous. The samples in this study were class X TKRO 1 and class X TKRO 2 because these two classes had the same number of students, namely 52 students. From the results of the data analysis that has been carried out, it can be stated that the level of students' scientific literacy abilities is 13.46% of students in the high category, 67.31% in the medium ability category, and 19.23% of students in the low category. On average, students' abilities are in the medium category.